Alternate bearing and phenology of ‘Valencia’ orange (Citrus sinensis [L.] Osbeck) in the lowland wet tropics of Colombia (2012)
In tropical conditions near the equatorial, precipitation is the main climatic factor that influences the growth and development of citrus plants. In a ‘Valencia’ orange orchard planted with 11-year-old trees located in the higher portion of the foothills of Corpoica, La Libertad Research Center in Villavicencio, Meta, Colombia, we recorded tree production data between the years 2008-2010. Information on the phenology of ten marked trees was gathered fortnightly from four cardinal directions using the methodology of Garrán et al. (1993) during the years 2009 and 2010. For this same period, the water balance was calculated for this orchard. The data were analyzed with descriptive statistics for most variables, and a mean-comparison test was carried out for the phenology observed at the cardinal points and for the correlation between annual precipitation and phenology. There was a positive correlation of 0.6 between rainfall and vegetative growth in 2009 and a negative correlation of -0.18 in 2010. There were no differences in phenology at the cardinal points. In 2008, the plants produced 168.8 kg/plant, causing the plants to present a strong vegetative growth and low yield (42.4 kg/tree) in 2009, whereas in 2010 there was an increase in the number of reproductive shoots, a decrease in the number of vegetative shoots and the harvest was 147.8 kg/tree. An alternation in the use of carbohydrates was observed between plant yield and vegetative growth.